SANGZOR VODIYSI TUPROQ QOPLAMINI ILMIY-AMALIY JIHATDAN TAHLIL QILISH - G‘o‘dalov, M.; Qosimov, N. (SCIENCE and SOCIETY, 2024)
In this article, the importance of soils its analyzed, in particular, soil types common in the Sangzor river basin, parent soil rocks found in mountainous and sub-montane proluvial plains, changes of soil towards elevations, and a map based on GAT were.